Dampak Fear of Missing Out (FOMO) terhadap Penyelesaian Tugas Akhir pada Mahasiswa Muslim Yogyakarta - Khalbi, Mutmainah; M. Suud, Fitriah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The phenomenon of Fear of Missing Out (FoMO) has become increasingly rampant among students, especially in the very high use of social media. This condition causes psychological pressure in the form of anxiety about being left behind from activities that others achieve. This research aims to understand and analyze the experiences of Muslim students who experience FoMO and how it affects students' productivity and academic focus. This study consisted of 7 informants by Muslim students who were in Yogyakarta and were around 19-22 years old. This research is also a qualitative research with a phenomenological approach that utilizes through semi-structured interviews with students who are pursuing their final projects and are active in using social media. The results of the study show that the most widely used platforms by students are WhatsApp and Instagram platforms where each data is 25%, and the duration of social media use in a day of 11-15 hours is 42.9%. Thus, there are several impacts, namely: (1) emotional, (2) academic distraction, (3) social comparison, (4) procrastination), (5) time management and discipline. Therefore, this study shows that FoMO has a great impact on the appearance of concentration disorders, anxiety, and less productive activities with peers. The implication of this research is that there is a need for special assistance related to emotional and digital literacy for students, so that the use of social media can be controlled in a healthy and good way without interfering with the academic process.